Topical Application of Tranexamic Acid in Abdominoplasties Leads to Lower Drainage Volume and Earlier Drain Removal - Isabel Zucal, MD; Laura De Pellegrin, MD; Alberto Pagnamenta, MD; Daniel Schmauss, MD; Davide Brucato, MD; Marco De Monti, MD; Riccardo Schweizer, MD; Yves Harder, MD; Corrado Parodi, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Tranexamic acid (TXA) is an antifibrinolytic agent that is successfully used in many medical fields to reduce blood loss. In plastic surgery, the systemic administration of TXA has been associated with less hematoma and seroma formation, and consequently, a reduction in the length of hospital stay (LOS). The aim of this study was to evaluate if the topical administration of TXA in patients undergoing abdominoplasty leads to a decrease in the daily drainage volume; earlier drain removal; and possibly, a shorter LOS. Methods:. In this single-center, comparative study, 60 patients undergoing abdominoplasty received either topical TXA treatment (n = 30; 1 g) or no treatment (n = 30). The primary endpoints were daily drainage volume, time until drain removal, and total LOS. Variables such as sex, age, body mass index, weight of resected skin and underlying fat, and concomitant liposuction were considered in the statistical analysis as covariates. Results:. In the TXA group, 54% less total drainage volume was observed (P < 0.01). The time until drain removal and LOS were reduced by 23% (P < 0.01) and 24% (P < 0.01), respectively, compared with the control group. Moreover, it was found that daily drainage volume increased with age. Conclusions:. Topical TXA administration reduces daily drainage volume, time until drain removal, and LOS significantly in patients undergoing abdominoplasty. Further studies analyzing the superiority of topical TXA compared with systemic TXA, as well as studies investigating the ideal TXA dosage could deliver further valuable information.